Konsep Pengendalian Diri dalam Perspektif Filsafat Stoisisme sebagai Pijakan Menjalani Kehidupan - Annisa Tri Ramadani (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the concept of self-control in the perspective of stoicism philosophy as a basis for living life. This study uses a qualitative method with a literature study approach. The concept of self-control in this study is a material object, whereas in the perspective of stoicism philosophy it is a formal object. The results and discussion show that the philosophical concept of stoicism is very important for the foundation of living human life, especially in how to control oneself so as not to cause anything unexpected and achieve happiness in one's life. In this study, the author recommends that readers learn, understand, and do what is contained in the concept of self-control in the perspective of stoicism philosophy as a basis for living life.